2000
DOI: 10.1046/j.1524-4725.2000.0260111041.x
|View full text |Cite
|
Sign up to set email alerts
|

Conscious Sedation of Pediatric Patients with Combination Oral Benzodiazepines and Inhaled Nitrous Oxide

Abstract: Monitored use of a combination of oral benzodiazepine and low to moderate concentrations of inhaled nitrous oxide can provide safe and effective conscious sedation in pediatric patients. Training in conscious sedation and emergency preparedness are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Midazolam is an alternative method [20][21][22][23][24] or a complement to EMLA for anxious children, but it has no analgesic effect, a slow onset, and a long duration of action; it can also be difficult to administer orally or rectally. More efficient analgesic alternatives, like morphine or pethidine, require monitoring and personnel resources which are not available in paediatric outpatient clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam is an alternative method [20][21][22][23][24] or a complement to EMLA for anxious children, but it has no analgesic effect, a slow onset, and a long duration of action; it can also be difficult to administer orally or rectally. More efficient analgesic alternatives, like morphine or pethidine, require monitoring and personnel resources which are not available in paediatric outpatient clinics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this medication is used for anxiolysis in children undergoing a variety of dermatologic surgical procedures. 10,11 As recommended by the FDA, oral midazolam should be used only in an outpatient setting that is equipped to provide continuous monitoring of respiratory and cardiac function. In addition, oral midazolam should be given only to a patient who will subsequently be monitored and observed directly by a health care professional.…”
Section: Discussionmentioning
confidence: 99%
“…In dermatology and dermatologic surgery, midazolam is used in adults for short procedures such as tumescent liposuction and ablative resurfacing. In addition, this medication is used for anxiolysis in children undergoing a variety of dermatologic surgical procedures 10,11 . As recommended by the FDA, oral midazolam should be used only in an outpatient setting that is equipped to provide continuous monitoring of respiratory and cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…During treatment the level of consciousness and co-operation was observed and recorded every 5 min guided by the six-point scoring scale (19)(20). The records showed that 72 of the 78 patients (92.3%) who completed the treatment under sedation were conscious and responsive to verbal contact and remained within the desired target Levels 3-4 during sedation.…”
Section: Discussionmentioning
confidence: 99%
“…sedation is considered unacceptable, such as in young children and in frail elderly patients. Conscious sedation with the use of i.v., intramuscular, oral, nasal or rectal sedative drugs [12][13][14][15][16][17][18] or tranquilizers combined with nitrous oxide, opioids or ketamine [19][20][21] has been previously reported. However, drug combinations result in an increased likelihood of complications particularly when used by inexperienced personnel.…”
Section: Introductionmentioning
confidence: 99%